2006
DOI: 10.2527/2006.842370x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gluconic acid on piglet growth performance, intestinal microflora, and intestinal wall morphology1

Abstract: Gluconic acid (GA) derives from the incomplete oxidation of glucose by some Gluconobacter strains. When fed to nonruminant animals, GA is only poorly absorbed in the small intestine and is primarly fermented to butyric acid in the lower gut. This study investigated the effect of GA on in vitro growth response and metabolism of swine cecal microflora and on animal growth performance, intestinal wall morphology, and intestinal microflora. During a 24-h in vitro cecal fermentation, total gas production and maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 36 publications
7
56
0
3
Order By: Relevance
“…The reason is probably that the function of GOD is to act as an antibacterial agent through the production of gluconic acid and H 2 O 2 . Biagi et al (2006) demonstrated that feeding gluconic acid positively influenced the composition and activity of the intestinal microflora of piglets after weaning. It has been reported that sustained oxidative stress through the maintenance of low concentration of H 2 O 2 by GOD's continued catalytic activity to be effective against pathogenic bacteria (Dobbenie et al, 1995;Wu et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is probably that the function of GOD is to act as an antibacterial agent through the production of gluconic acid and H 2 O 2 . Biagi et al (2006) demonstrated that feeding gluconic acid positively influenced the composition and activity of the intestinal microflora of piglets after weaning. It has been reported that sustained oxidative stress through the maintenance of low concentration of H 2 O 2 by GOD's continued catalytic activity to be effective against pathogenic bacteria (Dobbenie et al, 1995;Wu et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Two products of GOD hydrolysis are H 2 O 2 and gluconic acid, which may act as a bacteriocide (Crueger & Crueger, 1990;Rasiah et al, 2005;Costa et al, 2013) and acidity regulator (Nakao et al, 1997;Klein et al, 2002) to reduce the gastric pH, inhibit harmful bacteria and promote the growth of beneficial bacteria. Biagi et al (2006) reported that feeding gluconic acid can improve the growth performance of piglets after weaning. With large-scale production of GOD by fermentation, it is possible to achieve commercial application of GOD in the feed industry (Gao et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Da mesma forma, Biagi et al (2006) não notaram efeito dos níveis (0, 3, 6 e 12 ppm) de gluconato de sódio sobre a profundidade de cripta e altura de vilosidade do jejuno, íleo e ceco de suínos aos 70 dias de idade.…”
Section: Methodsunclassified
“…In addition, Ahmed et al (2014) stated that blends of organic acid supplementation reduce E. coli count and increase Lactobacilli population in weaned pigs. Biagi et al (2006) described a favourable effect of gluconic acid on intestinal microflora, morphology of intestinal villi, and general condition of piglets. Several studies documenting an improvement in growth efficiency have been reported in the literature (Missotten et al, 2009).…”
Section: Discussionmentioning
confidence: 99%